DEVELOPMENT OF MEDIUM AND SMALL BUSINESSES IN STAVROPOL REGION - E. Lepyakhova; E. Klimchenko; E. Sharunova; E. Ponomareva (Вестник Северо-Кавказского федерального университета)
The purpose of the article is a theoretical consideration of the aspects of the development of small and medium-sized businesses in Russia and in the Stavropol Territory. From the standpoint of the research methodology, a comprehensive economic analysis, comparison, and generalization of scientific and educational literature on the development of entrepreneurship were used. Empirical methods included: questionnaires, personal surveys of managers of small and medium-sized enterprises; author's monitoring of the development of medium and small businesses in the region. Descriptive statistics allowed us to generate quantitative data on the stated problem and present them in tables.